La cultura física, como elemento fundamental en la prevención de los niveles de sedentarismo en los alumnos del colegio experimental universitario “Manuel Cabrera Lozano” extensión Motupe, ubicada al norte de la ciudad de Loja, período 2013-2014 - Tamay López, José Darío (2014)
This research addresses PHYSICAL CULTURE AS A FUNDAMENTAL ELEMENT IN THE PREVENTION OF LEVELS SEDENTARISM IN COLLEGE STUDENTS UNIVERSITY EXPERIMENTAL MANUEL CABRERA LOZANO "The purpose of this research is aimed at obtaining a fair and realistic knowledge as a key element. Problems physical culture as essential to reduce and prevent sedentary levels, raising the level of effort to improve this problem element. Besides being a prerequisite to obtaining a Bachelor's Degree of Science in Physical Education, Culture mention requirement. The overall objective Meet the usefulness of the practice of physical culture as an essential element in the prevention of health problems that come with sedentary students specific objectives and know the different ways on how to prevent the problems of physical inactivity in education to investigate and determine the benefits that Physical Culture, to give a solution to problems associated sedentary methods, techniques and procedures used for the process of this research facility were inductive Method; Deductive method; Inductive Method; Hypothetical Deductive Method; Scientific method; Analytical Method; Description Method; was of great importance to be able to have real facts, applied a survey to prevent levels of physical inactivity that exists in the students of Manuel Cabrera Lozano Experimental College survey was administered to 60 students and 2 teachers and also used the technical record of observation; the survey and data collection were achieved results that allowed me to achieve test the hypotheses, the conclusions we have to conclude that recreational activities do help to leave the sedentary lifestyle is productive, distracts us, exercising more and practiced sport helps combat health problems since a person who is healthy and performing any activity body eliminates toxins and keep the body in good stress-free state.